(untitled) (Philological Studies, 2019)
The historical development of the Glagolitic and Cyrillic alphabets in Macedonian writings arose from the very beginning of Slavic literacy right through the Byzantine global strategic interests and the missionary work of Ss. ConstantineCyril and Methodius of Thessalonica. It was finally realized through the establishment and development of the Ohrid literary school and the work of Ss. Clement and Naum of Ohrid, as well as the continuing medieval written tradition of the Macedonian literary and scholastic centers. Specifically this paper addresses the differentiation of the written tradition in Macedonia and that of the other Southern-Slavic literary environments and Russia. The research is primarily devoted to the reflection of the mission to Moravia on the affirmation of the Slavic civilization and language; it also traces the historical relations to the earlier Slavic principality of St. Methodius in the Shtip-Strumica region and the centers that came after it in Preslav and Ohrid.